Pengembangan Bahan Ajar Untuk Meningkatkan Kemampuan Literasi Finansial Siswa SD - Ryfaldhi Wildan Maulana; K Kurniasih (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
In the 21st century, one of the life skills that students must master is financial literacy. However, the facts on the ground show that financial literacy material has not yet been included in learning in elementary schools. This study aims to develop teaching materials to improve the financial literacy skills of elementary school students. Based on the analysis of the social studies curriculum in grade IV elementary schools, there is no editorial related to financial literacy. One solution is the development of teaching materials. This teaching material was developed using the Design and Development method with the Richey Klein model. This model consists of planning, production, and evaluation stages. Data collection techniques used are literature study and expert validation. The research instruments needed are AMP sheets, teaching material structure sheets, and questionnaire sheets.